The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3390/molecules16032431
|View full text |Cite
|
Sign up to set email alerts
|

Bioflocculant Production by Virgibacillus sp. Rob Isolated from the Bottom Sediment of Algoa Bay in the Eastern Cape, South Africa

Abstract: A bioflocculant-producing marine bacterium previously isolated from marine sediment of Algoa Bay was screened for flocculant production. Comparative analysis of 16S rDNA sequence identified the isolate to have 99% similarity to Virgibacillus sp. XQ-1 and it was deposited in the GenBank as Virgibacillus sp. Rob with accession number HQ537127. The bacterium produced biflocculants optimally in glucose (70.4%) and peptone (70.4%) as sole sources of carbon and nitrogen, alkaline pH (12) (74%); and the presence of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 40 publications
4
81
2
1
Order By: Relevance
“…and Artrobacter spp. [92,93]. These findings imply that bacterial EPS effectively mediate flocculation and thus may be applied in large scale industrial processes, with particular reference to water and wastewater treatment.…”
Section: Future Prospects For Bacterial Epsmentioning
confidence: 83%
“…and Artrobacter spp. [92,93]. These findings imply that bacterial EPS effectively mediate flocculation and thus may be applied in large scale industrial processes, with particular reference to water and wastewater treatment.…”
Section: Future Prospects For Bacterial Epsmentioning
confidence: 83%
“…He et al [41] reported that glucose, sucrose and fructose were preferred carbon sources for REA-11 production, a bioflocculant produced by Corynebacterium glutamicum. It is well documented in the literature that many bioflocculant-producing microorganisms prefer organic carbon sources for optimum bioflocculant production [42]. However, the utilization of inorganic carbon sources for bioflocculant production is still scant in literature.…”
Section: Effect Of Carbon Source On Bioflocculant Productionmentioning
confidence: 99%
“…Nitrogen sources play a crucial role in the production of bioflocculants [42]. Different microorganisms utilize either organic or inorganic nitrogen sources, or both, to produce bioflocculants [43].…”
Section: Effect Of Nitrogen Source On Bioflocculant Productionmentioning
confidence: 99%
“…The result has been reported with bioflocculants production by Virgibacillus sp. Rob (Cosa et al 2011), Bacillus firmus (Salehizadeh and Shojaosadati 2002), and Enterobacter aerogene (Wenyu et al 2005). The glycosidase commonly present in the digestive systems of termite Nasutitermes takasagoensis degrades the cellulosic into glucose, while its activity was largely inhibited by the production of glucose (Tokuda et al 2009).…”
Section: Discussionmentioning
confidence: 98%